Covalent conjugation of cysteine-engineered scFv to PEGylated magnetic nanoprobes for immunotargeting of breast cancer cells. Issue 43 (14th April 2016) - Alric, Christophe; Aubrey, Nicolas; Allard-Vannier, Émilie; di Tommaso, Anne; Blondy, Thibaut; Dimier-Poisson, Isabelle; Chourpa, Igor; Hervé-Aubert, Katel
Abstract : Orientation- and site-directed covalent conjugation of cysteine-engineered scFv to PEGylated SPIONs allows antigen recognition while preserving colloidal properties of nanoprobes. Abstract : In the present study, we describe the synthesis and characterization of new generation of cancer-targeting magnetic nanoprobes: superparamagnetic iron oxide nanoparticles (SPIONs) coated with polyethylene glycol (PEG) shell functionalized with recombinant anti-HER2 single chain fragment variable (scFv) of Trastuzumab antibody. An anti-HER2 scFv with terminal cysteine (scFv 4D5-Cys) has been rationally engineered in order to favor its orientation- and site-directed covalent conjugation to the polymeric surface of PEGylated SPIONs. Optimization of scFv and nanoparticles production allowed to obtain well-characterized SPIONs-PEG–scFv nanoparticles carrying ∼7 fragments per nanoparticle, having a hydrodynamic diameter of ca. 86 nm and nearly neutral surface. The nanoprobes-scFv capability to recognize the HER2 protein has been confirmed by enzyme-linked immunosorbent assay (ELISA). Compared to non-targeted PEGylated SPIONs, the SPIONs–PEG–scFv nanoprobes showed an enhanced binding to HER2-overexpressing cells (SK-BR3) in vitro as it was shown by immunofluorescence. Finally, ICP-AES measurements shown that in 1 hour the uptake of SPIONs–PEG–scFv in HER2-overexpressing cells is 2.1 times greater than non-targeted PEGylated SPIONs. Therefore, both due to their physico-chemical characteristics and the immunotargeting of HER2-positive breast cancer cells, the SPIONs–PEG–scFv appear as promising nanoplatforms for future applications in theranostic treatment of cancers.